How do Families Assess and Manage the Pain of Cancer Patients? - Titan Ligita; Ariyani Pradana Dewi; Tri Rina Febriyanti (Universitas Airlangga, 2014)
Introduction: Pain assessment and pain management for patients living with cancer performed by nurses have been improved gradually. This strategy needs the roles of both nurses and families of patients living with cancer. Prior to the application of effective pain management, it is vital to perform pain assessment. The involvement of families in patients care may assist nurses to optimize caring and thus the patients are monitored continuously. But, there is still limited study about the involvement of families in pain assessment and pain management. This study was aimed to explore how the family performed pain assessment and pain management for patients living with cancer.Method: This was a phenomenology study and also used purposive sampling methods. Participants were family members of patients living with cancer around Pontianak - Indonesia. The datas were collected through in-depth interview in order to revealed some themes/context and was analyzed through Thematic Analysis.Result: The highlighted contexts in this study were the meaning of pain, the impact of pain, the process of pain assessment and pain management carried out by the families, as well as the facilitating factors and the barriers in assessing and managing the pain.Discussion: Experiences of the families in assessing and managing the pain may provide information for nurses about how to fulfil the needs of the family on skills needed. Therefore, the consistency and continuity of pain assessment and pain management are important. Consequently, the nurses must ensure that the family are ready to take care the patients, so that the pain control can be optimal dn side effects can be avoided. The accurity of information about the patients provided by the family may determine the nurse to make decisions in providing best practice for the patients in controlling their pain.